Fingertip Replantation with the Use of a Long Vein Graft: Training Young Surgeons in a Feasible Technique to Maintain Optimal Results - Shiraishi, Tomohiro; Kurita, Masakazu; Narita, Keigo; Takushima, Akihiko; Harii, Kiyonori (Journal of Reconstructive Microsurgery Open, 2016)
Background Fingertip replantation has become a standard operation for well-experienced microsurgeons, but naturally there are some unsuccessful cases. Furthermore, younger surgeons need experience with this procedure, as replantations are often an emergency operation and experts may not be available to attend. Therefore, we reviewed our cases to determine the most effective procedure that can enable young surgeons to obtain a good outcome.Methods We retrospectively investigated 69 fingertip replantation cases treated between January 2006 and December 2014 at the Kyorin University Hospital. All operations were performed by several young surgeons who were instructed by one experienced surgeon (the principal author, T.S.). In this study, cases were divided into three groups according to vein graft usage. In group A, a long vein graft that reached the proximal phalanx was employed. In group B, a short vein graft that was almost as long as the arterial defect was employed. In group C, no vein graft was used. The differences in the survival rates of the fingertips between the groups were analyzed.Results The total fingertip survival rate was 93% (64 out of 69). All 42 (100%) fingertips in group A survived, 5 of 6 (83%) fingertips in group B survived, and 17 of 21 (81%) fingertips in group C survived.Conclusion Preferential use of a long vein graft could provide superior results and enable young surgeons to perform successful fingertip replantations, as it is a reliable and relatively an easy procedure compared with other techniques.
Keywords: fingertip replantation; long vein graft; training